Arterial Lactate Concentration at the End of Liver Transplantation Is an Early Predictor of Primary Graft Dysfunction. Issue 1 (July 2019) - Golse, Nicolas; Guglielmo, Nicola; El Metni, Albert; Frosio, Fabio; Cosse, Cyril; Naili, Salima; Ichaï, Philippe; Ciacio, Oriana; Pittau, Gabriella; Allard, Marc-Antoine; Castaing, Denis; S. A. Cunha, Antonio; et al.
Abstract : Background: Although many prognostic factors of primary graft dysfunction after liver transplantation (LT) are available, it remains difficult to predict failure in a given recipient. Objective: We aimed to determine whether the intraoperative assay of arterial lactate concentration at the end of LT (LCEOT) might constitute a reliable biological test to predict early outcomes [primary nonfunction (PNF), early graft dysfunction (EAD)]. Methods: We reviewed data from a prospective database in a single center concerning patients transplanted between January 2015 and December 2016 (n = 296). Results: There was no statistical imbalance between the training (year 2015) and validation groups (year 2016) for epidemiological and perioperative feature. Ten patients (3.4%) presented with PNF, and EAD occurred in 62 patients (20.9%); 9 patients died before postoperative day (POD) 90. LCEOT ≥5 mmol/L was the best cut-off point to predict PNF (Se=83.3%, SP=74.3%, positive likelihood ratio (LR+)=3.65, negative likelihood ratio (LR−)=0.25, diagnostic odds ratio (DOR)=14.44) and was predictive of PNF ( P = 0.02), EAD ( P = 0.05), and death ⩽ POD90 ( P = 0.06). Added to the validated BAR-score, LCEOT improved its predictive value regarding POD 90 survival with a better AUC (0.87) than BAR score (0.74). The predictive value of LCEOT was confirmed in the validation cohort. Conclusion: As a reflection of both hypoperfusion and tissue damage, the assay of arterial LCEOT ≥5 mmol/L appears to be a strong predictor of early graft outcomes and may be used as an endpoint in studies assessing the impact of perioperative management. Its accessibility and low cost could impose it as a reliable parameter to anticipate postoperative management and help clinicians for decision-making in the first PODs.